2021
DOI: 10.1111/fwb.13706
|View full text |Cite
|
Sign up to set email alerts
|

Potential long‐distance dispersal of freshwater diatoms adhering to waterfowl plumage

Abstract: Waterfowl are potential long‐distance dispersal vectors for aquatic microbes such as diatoms, but supporting empirical data are scarce, especially concerning external transport on feathers. We conducted an experiment designed to partially emulate diatom dispersal via adherence to waterfowl, and to evaluate the effects of relative humidity (RH) and exposure time on viability. We dipped individual breast feathers from mallards (Anas platyrhynchos) in a pure culture of the freshwater diatom Nitzschia pusilla Grun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Both epizoochory and endozoochory are important for microbial dispersal by waterbirds, but it is unclear which mechanism is dominant. Manning et al (2021) investigated the potential of epizoochory by dipping breast feathers from mallards Anas platyrhynchos in cultures of diatoms and showed that their survival when stuck to feathers increases with relative air humidity. Tesson et al (2018) used in vitro gut-simulation to investigate the endozoochory potential of dinoflagellates, confirming that resting cysts survived gut conditions.…”
Section: Under S Tudied Role Of Waterb Irds a S Vec Tor S For Microb E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Both epizoochory and endozoochory are important for microbial dispersal by waterbirds, but it is unclear which mechanism is dominant. Manning et al (2021) investigated the potential of epizoochory by dipping breast feathers from mallards Anas platyrhynchos in cultures of diatoms and showed that their survival when stuck to feathers increases with relative air humidity. Tesson et al (2018) used in vitro gut-simulation to investigate the endozoochory potential of dinoflagellates, confirming that resting cysts survived gut conditions.…”
Section: Under S Tudied Role Of Waterb Irds a S Vec Tor S For Microb E Smentioning
confidence: 99%
“…Sensitivity analysis for wintering waterbirds suggests that maximum gut retention times have less influence on seed dispersal kernels than the nature of bird movements per se, reinforcing the need to include quality tracking data to obtain valid predictions (Martín-Vélez, Leeuwen, et al, 2021). Some studies of endozoochory have made unrealistic estimates of the scale of dispersal, as they fail to accurately account for waterbird movement, and make simple extrapolations from a retention time curve by assuming propagule ingestion is followed by non-stop flights (e.g., Manning et al, 2021;Raulings et al, 2011). However, ringing recoveries have been used to make general predictions for kernels during seasonal migration, and have shown that migrating ducks can facilitate dispersal on a very large scale, predicting dispersal of over 3.5% of seeds to be over 100 km and up to 1,600 km, although maximum dispersal distances for Artemia cysts were about half that of seeds (Viana et al, 2013).…”
Section: Under S Tanding Waterb Ird Movements and Modelling Zoochorymentioning
confidence: 99%
“…Cosmopolitanism is particularly limited between continents (less than 3%), whereas when considering climate zones, the subpolar (Fennoscandia) and temperate (France) zones – both located in Europe, shared 10% of the genetic variants. Such higher similarity is related to their close geographic location and strong connection by land that facilitate the transportation of freshwater diatoms (Manning et al, 2021). The case of the tropical continental samples (South America and Africa) is interesting: these two continents, which belong to the same climate zone, are separated by ca.…”
Section: Discussionmentioning
confidence: 99%
“…They are unicellular eukaryotic microalgae with large taxonomic diversity and marked species‐specific ecological preferences. The ability of diatoms to disperse through the air or through animal transportation is critical for the colonization of new locations (Manning et al, 2021). Still, not much is known about the geographic range and rate of diatoms' dispersal and their effects on the dynamics of communities across landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Since connectivity plays an important role in structuring aquatic communities in TRs (Cid et al, 2022), the focus was on two groups of organisms with contrasting dispersal abilities: diatoms and macroinvertebrates. Diatoms are widely dispersed (Bogan et al, 2017; Kristiansen, 1996) by water flow, wind, or animal vectors such as mammals and birds (Leone et al, 2014; Liu et al, 2013; Manning et al, 2021; Romero et al, 2003). Macroinvertebrates have two main dispersal modes (Bilton et al, 2001): i) active dispersers (e.g., adult dragonflies) can reach very long distances and they usually fly oriented upstream (Bogan & Boersma, 2012; French & McCauley, 2019); whereas ii) passive dispersers (e.g., larvae of non‐biting midges) might drift downstream (Brown et al, 2011; Sarremejane et al, 2020) or restrict their movements to the benthic zone (Kappes & Haase, 2012).…”
Section: Introductionmentioning
confidence: 99%